2015
DOI: 10.1088/1742-5468/2015/12/p12006
|View full text |Cite
|
Sign up to set email alerts
|

The solution space structure of random constraint satisfaction problems with growing domains

Abstract: In this paper we study the solution space structure of model RB, a standard prototype of Constraint Satisfaction Problem (CSPs) with growing domains. Using rigorous the first and the second moment method, we show that in the solvable phase close to the satisfiability transition, solutions are clustered into exponential number of well-separated clusters, with each cluster contains sub-exponential number of solutions. As a consequence, the system has a clustering (dynamical) transition but no condensation transi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…[19], Bethe free entropy was studied, and it was suggested that the RS solution should always be stable locally; thus, the condensation transition should be absent in this model. In article [20], we indeed prove that the clustering phase exists and persists until the satisfiable-unsatisfiable transition point, so the condensation phase do not exist. The solution space of model RB is quite different from that of other CSPs such as K-SAT or Coloring, where the condensation transition is observed [6].…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…[19], Bethe free entropy was studied, and it was suggested that the RS solution should always be stable locally; thus, the condensation transition should be absent in this model. In article [20], we indeed prove that the clustering phase exists and persists until the satisfiable-unsatisfiable transition point, so the condensation phase do not exist. The solution space of model RB is quite different from that of other CSPs such as K-SAT or Coloring, where the condensation transition is observed [6].…”
Section: Introductionmentioning
confidence: 75%
“…Clustering range Cluster diameter ≤ Distance among cluster-regions ≥ Number of clusters [20] r0 < r < 1 a2n (b2 − a2)n exponential In Table II [20]. We have the following observations.…”
Section: Casesmentioning
confidence: 82%
See 1 more Smart Citation
“…It has been shown that random instances of model RB are hard to solve at the threshold both theoretically [6] and experimentally [7], thus benchmarks based on model RB have been widely used in algorithm competitions. In addition, studies on the statistical mechanics of model RB show that the replica symmetry solution is always stable in the satisfiable phase [10,11], and there is no condensation transition in model RB [8].…”
Section: Introductionmentioning
confidence: 99%
“…Model RB has been proved to have sharp SAT-UNSAT phase transition and exact threshold points, and can generate hard instances in the phase transition region [12,14]. In addition, it was proved that model RB has a clustering transition but no condensation transition [17,16]. Moreover, randomly generated forced RB instances with one hidden solution are proved to have both similar distribution of solutions and hardness property with unforced satisfiable RB instances [15].…”
Section: Introductionmentioning
confidence: 99%